2001
DOI: 10.2307/3285075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron on the Virulence of Trichomonas vaginalis

Abstract: The role of iron was evaluated with respect to the virulence of Trichomonas vaginalis in mice. Iron-supplemented and iron-depleted Diamond's trypticase-yeast extract-maltose (TYM) media were prepared by adding 360 microM of ferrous sulfate and 100 microM of 2,2'-dipyridyl. Trophozoites cultivated from normal TYM and iron-supplemented TYM media produced subcutaneous abscesses; however, trichomonads grown in an iron-deficient TYM medium failed to produce any pathology. In addition to the increased virulence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 0 publications
1
36
1
Order By: Relevance
“…These proteins interact with host cells via ligand-receptor-type interactions [17]. Furthermore, it has been reported that transcription and expression of genes coding for these proteins are greatly influenced by iron concentration in the medium where the protozoan was cultivated [18][19][20]. Pathogenicity is also influenced by cellular contact between pathogens and the epithelial cells, culminating in disturbance of the junctional complex [14,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…These proteins interact with host cells via ligand-receptor-type interactions [17]. Furthermore, it has been reported that transcription and expression of genes coding for these proteins are greatly influenced by iron concentration in the medium where the protozoan was cultivated [18][19][20]. Pathogenicity is also influenced by cellular contact between pathogens and the epithelial cells, culminating in disturbance of the junctional complex [14,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The role of iron in T. vaginalis has been shown to be associated with the virulence of the parasite in mice [7]. In addition to the increased virulence, iron also enhances the level of adherence and the cytotoxicity of Trichomonads [7].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the increased virulence, iron also enhances the level of adherence and the cytotoxicity of Trichomonads [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations